Keragaman Genetik dan Pengembangan Perangkat Penanda Molekuler untuk Deteksi Dini Bibit Berdasarkan Kematangan Awal Tanaman Kelapa Sawit (Arenga pinnata Merr.) di Indonesia: Sebuah Tinjauan - Kristianto Nugroho; Amalia Prihaningsih; Rerenstradika Tizar Terryana; Mastur; Puji Lestari (Buitenzorg: Journal of Tropical Science, 2026)
Sugar palm (Arenga pinnata Merr.) is a promising estate crop with significant potential as a raw material for palm sugar, starch, fiber, and bioethanol production. However, its utilization and cultivation in Indonesia have not been fully optimized. This plant is found throughout Indonesia's tropical rainforests, from Sumatera to Papua. While several genetic diversity studies of sugar palm in Indonesia have been conducted using morphological traits, isozymes, and molecular markers, these efforts are less extensive than those focused on other members of the Arecaceae family. To date, the genetic diversity studies of sugar palm in Indonesia are still limited in terms of the number of markers, population coverage, and the use of modern genomic approaches. This paper aims to review the current status of genetic diversity research on sugar palm in Indonesia and the development of a molecular marker toolkit for the early identification of early maturing sugar palm seedlings.. The introduction of this toolkit is expected to accelerate sugar palm breeding programs in Indonesia, particularly in developing improved varieties that can benefit farmers. Further dissemination and broader availability of this kit are necessary to increase recognition of its benefits and facilitate its widespread adoption within the community.   Keywords: detection toolkit, genetic diversity, molecular marker, plant breeding, estate crop